Factores de riesgo relacionados con el retraso psicomotor en niños atendidos en el centro de salud Puertas Negras, Cantón Babahoyo, los ríos, noviembre 2023 - abril 2024. - Lamilla Dávila, María Fernanda (2024)
The study focused on identifying risk factors related to psychomotor delay in children treated at the Puertas Negras Health Center, located in Babahoyo, Los Ríos, between November 2023 and April 2024. The importance of addressing these factors is recognized. to intervene early and prevent complications in child development. The research, following ethical and methodological criteria, seeks to provide information to improve care and promote the health of children in this community by nursing staff. Data collection was carried out through surveys using a questionnaire divided into dimensions such as functional dynamics and prenatal, perinatal and postnatal history to evaluate knowledge about early stimulation and risk factors related to psychomotor delay in children treated at the health center. mentioned. The results were analyzed with Microsoft Excel, observing the main risk factors that influence psychomotor delay in children treated at the Puertas Negras Health Center. The conclusions highlight the importance of early stimulation programs carried out by nursing staff to prevent and control psychomotor delay in children, as well as the need for mothers to attend prenatal check-ups to avoid problems at the time of delivery.